cAMP export by the fission yeast Schizosaccharomyces pombe - Eberhard, Jeremy (MicroPubl Biol, 2021)
The fission yeast Schizosaccharomyces pombe produces a cAMP signal in response to glucose detection. Previous characterization of this signaling focused on intracellular levels of cAMP. Here, we find that the cAMP is secreted into the medium almost immediately. This is not due to PKA activation as might have been expected. In addition, a strain that is highly deficient in drug efflux shows only a modest reduction in the secretion of cAMP to the growth medium. These observations reveal a previously unappreciated aspect of cAMP metabolism in an important model organism, leading to new questions regarding the mechanism and benefit of cAMP export in S. pombe.